Pengembangan Program Peningkatan Pendapatan UMKM Ibu Rumah Tangga Melalui Inovasi dan Modifikasi Produk Donat Toping - Nelson Jafridin; Nurul Hidayat; Liska Pasorong; Yulita Lidan; Gloria Tabita Temban; Shalsa Khayrtaul Azisah (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
This program aims to increase the income of MSME housewives through innovation and modification of donut topping products. This program is designed to empower housewives with new skills in making and marketing more interesting and varied donuts. Through training and mentoring, it is hoped that housewives can improve the quality of their products, attract more customers, and ultimately increase family income. The method used to develop the Skills Training Program is the Participatory Action Research (PAR) approach. This approach involves the active participation of SME owners, namely housewives, as program stakeholders. Data collection techniques include interviews, surveys and observations, while the data collected will be analyzed qualitatively by coding data and compiling narratives to identify relevant problems and solutions. The result of this work, namely the UKM skills improvement program for housewives, is a comprehensive initiative that involves the active participation of UKM owners and stakeholders. This includes technical, managerial, financial and financial literacy training to increase production and competitiveness of SMEs. The program also covers aspects such as information technology, social skills, environmental sustainability and collaboration to empower SMEs as a whole. With this holistic approach, it is hoped that SMEs can develop and contribute to local economic growth and have wider market opportunities, especially for housewives in general.